ANALISIS USAHA DAN POTENSI PENGEMBANGAN KERAMBA JARING APUNG (KJA) DI WADUK PLTA KOTO PANJANG KABUPATEN KAMPAR PROVINSI RIAU - Hendrik Hendrik (Berkala Perikanan Terubuk, 2012)
This research aims to know KJA effort feasibility and development potency atPLTA Koto Panjang. Result of this research showed if KJA'S effort with 10reasonable bags to be developed by investments as big as Rp 118.625.000,- withonce time harvests as big as Rp 24.524.000,in a year is done crop thrice.Development potency KJA stills outspread base environmental advocate energywith level harnessed new accumulating basin 5,1% by total KJA now 1.000 bag.about problem on a long term is accessibility stock down that until now still iswreaked from pasaman sumatra smolders and be made its accumulatings basinspatial manner for developmental KJA and another activity.